(untitled) (Revista Brasileira Multidisciplinar, 2010)
Soils from the National Forest of Tapajos are nutrient-poor, acidic, podzolic clay types, with high aluminum content. The Dry Forest Project was developed to assess the impact of drought on a tropical forest. This project includes plots of Primary Forest (FP, control) and Dry Forest (FS, with exclusion of rain). This study assessed the effect of dryness on the microbial populations of soils collected in these plots. Twelve soil samples were analyzed for counts of total bacteria, fungi, and cellulolytic, proteolytic and phosphate solubilizer populations. A decrease of microbial counts was detected at the dry forest plot in comparison with the control, being more significant (two orders of magnitude) for cellulolytic populations. The majority of 286 isolated cultures were Gram-positive bacilli (47% for FP and 62% for FS) and the prevalent genera were Bacillus, Corynebacterium, Listeria and Micrococcuss. Box-PCR profiles of the bacteria from both plots showed high genetic diversity. The exclusion BATISTA, Selma Baia Centro de Ciências Biológicas e da Saúde (CCBS) Universidade Federal do Mato Grosso. Av. Fernando Correia da Costa. Bairro Boa Esperança, Cuiabá-MT. CEP 78060-900. Brasil. Tel. (65) 63615-8970. E-mail: selbbat@yahoo.com.br HARGREAVES, Paulo Iiboshi; MENDONÇA-HAGLER, Leda Cristina Instituto de Microbiologia Prof. Paulo de Góes (IMPPG) UFRJ; Laboratório de Ecologia Microbiana e Taxonomia; Centro de Ciências da Saúde (CCS), Bloco I, sala 44, Ilha do Fundão-RJ. CEP 21941-590. Brasil. Tel. (21) 2562-6739. SOUSA, Oscarina Viana de Instituto de Ciências do Mar – LABOMAR UFC; Av. da Abolição, 3207 – Meireles – Fortaleza-CE. CEP 60165-081. Tel. (85) 3366-7000 of rain can produce a negative effect on the microbial populations of tropical forest soil. The diversity, at the genus level, does not appear to be affected by drought, and the high diversity found for bacteria at the species/ subspecies level at both sites suggested a resilience of the soil microbiota to this environmental stress.